Evaluation of Trichoderma in Three Peanut Varieties (Arachis hypogaea L.) - Vera-Cruz, Edison Fabricio; Quevedo-Guerrero, José Nicasio; Tuz-Guncay, Ivanna Gabriela; Chabla-Carillo, Julio Enrique; Cuenca-Sedamanos, John Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Bearing in mind that peanut cultivation in Ecuador has lost agricultural interest due to its susceptibility to fungal diseases, and that the application of microorganisms of the genus Trichoderma effectively controls other species of pathogens, we decided to carry out this study. For this, the Plant Health Laboratory and the experimental area of “Santa Inés” farm of the Faculty of Agricultural Sciences at the Technical University of Machala were used. A completely randomized block design was employed, with 33 treatments, four Trichoderma and its mix strains, two concentrations (1011 and 1012 spores/L) on three peanut varieties (INIAP 380, 381 and 382), three controls, with three replicates, evaluating 15 plants per dose, giving a total of 495 plants. The variables evaluated were plant height (cm), main branches/plant, 100 seed weight (g), nodule weight (g), number of seeds/pod, number of seeds/plant, number of pods/plant, seed weight per plant, rust incidence and white mold incidence. The results obtained indicated that the application of Mix increased production in all varieties and decreased the incidence of rust (Puccinia arachidis) by 55% and white mold (Sclerotinia sclerotiorum) by 53% compared to the controls.